TEKNOLOGI PENANGGULANGAN DAN PENGENDALIAN KERUSAKAN LINGKUNGAN PESISIR, PANTAI DAN LAUT UNTUK MENDUKUNG PENGEMBANGAN PARIWISATA - Nawa Suwedi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Erosion, sedimentation, sea level rise, tsunami, sea water pollution, coralreef and mangrove forest destruction are problems, that have to beconsidered during planning, development and management of the coastal,sea and marine tourism activity. Alternative technology such as naturaland man made coastal and sea protections (revetment, bulkhead, seawall, jetty, groin, breakwater, submerged artificial reef, oil boom, oilskimmer) and information technology can be used and applied for thispurpose.